Theonyms in religious dastans - Кәрібай, Қ.С.; Zhakupov , Ж.А. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2022)
Theonyms for Kazakh linguistics are a relatively new object of lexicology. They occupy a special place in the vocabulary of the Kazakh language. From the point of view of religious studies, they have a terminological character; from the point of view of literary language, they have a passive, borrowed vocabulary; from a stylistic point of view, they form a special substyle; from the point of view of nomination, they have the character of both proper and common names. Therefore, at the first stage of the study, it is necessary to observe the way they enter the vocabulary of the Kazakh language. Religious folklore contributes to this task. Therefore, the linguistic facts of religious dastans as a space for the application of theonyms are brought to the analysis. Religious dastans are a folklore genre that occupies a special place in oral folk art. The basis of Kazakh religious dastans are Muslim legends and myths, the principles of the Koran, the Sunnah of the Prophet and hadith, legends about Muslim figures and Islamic heroes. The thematic range of religious dastans is very wide: narratives about Muslim heroes, Holy War, service to the Prophet, etc. All of them are dedicated to a specific goal – the popularization and propaganda of Islam. In this regard, we consider it relevant to study the language of religious works. And the lexical groups that distinguish the language of religious dastans are theonyms. Theonyms are often found in Kazakh religious folklore, especially in religious dastans. The article contains theonyms in religious dastans, which are divided into words that have meaning with the word of God, the names of angels, the names of prophets and the names of the companions of the prophet. The theonyms of each group are given examples from religious epics, and each lexeme is analyzed separately, while the authors tried to give an interpretation and etymological observations.